Metabolic Syndrome, Kidney-Related Adiposity, and Kidney Microcirculation: Unraveling the Damage - Kyu Won Jang; Jin Hur; Dong Won Lee; Seo Rin Kim (Biomedicines)
Metabolic syndrome (MetS) is a cluster of interrelated risk factors, including insulin resistance, hypertension, dyslipidemia, and visceral adiposity, all of which contribute to kidney microvascular injury and the progression of chronic kidney disease (CKD). However, the specific impact of each component of MetS on kidney microcirculation remains unclear. Given the increasing prevalence of obesity, understanding how visceral fat—particularly fat surrounding the kidneys—affects kidney microcirculation is critical. This review examines the consequences of visceral obesity and other components of MetS on renal microcirculation. These kidney-related fat deposits can contribute to the mechanical compression of renal vasculature, promote inflammation and oxidative stress, and induce endothelial dysfunction, all of which accelerate kidney damage. Each factor of MetS initiates a series of hemodynamic and metabolic disturbances that impair kidney microcirculation, leading to vascular remodeling and microvascular rarefaction. The review concludes by discussing therapeutic strategies targeting the individual components of MetS, which have shown promise in alleviating inflammation and oxidative stress. Integrated approaches that address both of the components of MetS and kidney-related adiposity may improve renal outcomes and slow the progression of CKD.